Współpraca przedsiębiorstw z jednostkami naukowymi w warunkach niestabilnego otoczenia - Joachimiak, Izabela; Karpińska, Marzena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Due to EU funds, nowadays exists a lot of opportunities in Poland to receive benefits from support of the development co-operation between science and business. Nevertheless, the experience of Western Europe countries shows that the same financial backing is not enough, because the necessary co-operation mechanisms and a change in social awareness, which could be achieved by using regulatory incentives to establish co-operation in order to raise a level of innovation in Poland are too small. European programs and national sources are a very good starting point to set up a co-operation between science and business, especially when the economic situation in the world is tenuous. It is surprising that in case of research and development activities the economic crisis has not weakened innovations but on the contrary, worked like a catalyst, thereby led to creation the entirely new technologies.
Keywords: research institutions; research and development; economic crisis